Fantasmagorias de um pintor exótico: o grotesco insólito no Ensaio sobre a Cegueira - Carmo, Maria José do (2006)
This research takes charge of an interpretative analysis of the novel Ensaio sobre a Cegueira (1995) by the Portuguese author José Saramago, and uses as the main stream of this assignment the aesthetic construction of the grotesque, imbricated in the allegory, as metaphor of the white blindness that conducts the narrative. In the analysis of the corpus, we use as main theoretical reference the works of Mikhail Bakhtin: A cultura popular na idade média e no Renascimento and Problemas da poética de Dostoiéviski, and the one by Wolfgang Kayser: O Grotesco, where we tried to follow the aesthetic of the grotesque path to the white blindness unveiling established in that saramaguian narrative. In the first chapter, we have made a theoretical outline of the allegory, the grotesque and the menipeia satire, to give analytical support to the second chapter, where we has, more often, used the particularities of the corpus in the novel. In the selection of this corpus, we sought to draw comparisons with canvas of several styles, to the interpretation of the dialogue that is stablished between the Poetuguese author s writing and some procedure of the expressionism. At last we also thought it was necessary to attach the genesis of creation of that novel to the assignment, for a better support to the studying object